Subtle‐but‐smouldering myocardial injury after immune checkpoint inhibitor treatment accompanied by amyloid deposits - Mizuki Ida; Shiro Nakamori; Shinya Yamamoto; Seimi Watanabe; Kyoko Imanaka‐Yoshida; Masaki Ishida; Hajime Sakuma; Keiichi Yamanaka; Kaoru Dohi (ESC Heart Failure)
Abstract Although cardiac troponin is a highly specific biomarker for myocardial cell injury, it is important to recognize the pitfalls of this test in the diagnosis and management of immune checkpoint inhibitor (ICI) myocarditis. We describe the challenging case of an 81‐year‐old woman with persistently high troponin after undergoing immunotherapy with ipilimumab and nivolumab, and histological evidence of amyloid deposition in the myocardium. The patient received immunosuppressive treatments based on the magnitude of troponin changes because myocarditis was clinically suspected. However, histological examination revealed the deposition of transthyretin amyloid fibrils with only minimal T‐lymphocyte infiltration and no myocyte necrosis, suggesting transthyretin cardiac amyloidosis rather than ICI myocarditis. This case highlights the importance of assessing other causes of persistently high troponin, and the necessity of incorporating comprehensive histological and immunohistochemical examinations of the endomyocardial biopsy, especially when cardiovascular magnetic resonance imaging is inconclusive.